Fluorescence polarization method for detection of lard mixed with olive oil. Issue 1 (February 2021) - Salsabila, A; Azam, M; Sugito, H; Soesanto, Q M B; Firdausi, K S
Abstract: This study is based on fluorescence polarization as a potential alternative method for an investigation of contamination of lard in food. The purpose of this study was to obtain the characteristic of fluorescence polarization in olive oil samples mixed with lard. The characteristics of fluorescence polarization were obtained by measuring changes in the polarization of light using a linearly polarized green laser pointer and observed in the direction of the scattering angle of 90˚ for various direction of electric field of the laser. The results showed that the critical angle of direction of electric field of the laser and the average polarization change increase as the concentration of lard is raised. It could be due by additional asymmetric triglycerides and molecular orientation that play an important role in the sample. This result shows that additional mixture of lard in olive oil can be detected, and this method seems to be developed for the detection of low concentrations of lard contamination.